STUDENTS’ ANXIETY IN SPEAKING ENGLISH DURING ONLINE CLAS - Suci Aprilia Ningsih; Iswandini Agustin (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This research is focused on identifying the factor of students’ anxiety in speaking English during online class. This research used descriptive qualitative research design. The object on the 10th grade of Senior High school. The researcher employing observations, interviews to collect data and data analysis in this research was descriptive analysis, data display, conclusion or verification and triangulation. The researcher hopes this study will be useful as guidance for the teacher, researcher and the other, and make the teachers realize that speaking anxiety gave an influence on speaking performance especially in online class teaching, and the teacher should be more creative to teach their students and make them be more confident to speak English based on the factors caused the students anxiety in speaking English during online class